Effects of salvadora persica extract on the bacterial population in single-species biofilm - Fatin-Majdina, N.; Zubaidah, A.R.; Munirah, A.R.M.; Marina, M.B. (Penerbit Universiti Kebangsaan Malaysia, 2014)
The effect of S. persica extract on the population of bacteria in single-species biofilm was investigated. An artificial mouth (NAM) system was used for the development of biofilm. In one experiment, aqueous extract of S. persica at sub-MIC concentration (5 mg/mL) was first pumped into the NAM system to treat the experimental pellicle on glass beads before inoculating it with the bacteria (Strep. mitis, Strep. mutans and Strep. sanguinis). This would resemble using the aqueous extract of S. persica before meals. In another experiment, the aqueous extract of S. persica was pumped into the NAM system after the bacterial inoculation and this would resemble using it after meals. In both experiments, 24 h biofilms were allowed to form. The bacterial population of the biofilms was determined and expressed as colony forming unit per mL (cfu mL(-1)). For negative control, sterilized distilled water was used whereas for positive control, commercial Listerine. It was found that the population of Strep. mitis, Strep. mutans and Strep. sanguinis in the respective biofilms for both experiments involving treatment with S. persica extract or Listerine was significantly reduced by more than 70% (p< 0.05) when compared with the negative control. Comparing the effect of S. persica with Listerine on the bacterial population of the biofilms when used either before or after meal showed that S. persica is slightly less effective towards S. sanguinis before meal and towards S. mutans after meal (p< 0.05). This study suggests that the efficiency of the antibacterial effect of S. persica is species-related and by its way of usage.